Perancangan Pembangkit Listrik Tanpa BBM Untuk Penerangan Kapal Nelayan dan Rumah Penduduk Serta Meningkatkan Kesejahteraan Ekonomi Kelompok Pedagang Gorengan Di Kelurahan Manggar - Andi Sri Irtawaty; Lilik Damayanti; Subur Mulyanto (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2020)
Electrical energy is a primary need in modern human life. As the population increases, the demand for electricity will also increase. Under certain conditions, especially for groups of fishermen and fried food traders, especially at night, of course, requires additional equipment that requires fuel oil (BBM) as a source of lighting energy. Based on the field survey, in a month fishermen use 20 liters of diesel x 30 days x Rp. 6000, - = Rp. 3,600,000 to move the generator engine. Therefore, the Balikpapan State Polytechnic PkM team innovated to design a fuelless power plant with a capacity of 300 watts and 1000 watts assembled from a 12 volt 5A battery for a 300 watt inverter and a 12 volt 8A battery for a 1000 watt inverter. The design of this tool is presented in practical form at PkM activities for 3 working days (2 days offline and 1 day online) in Manggar Village which was attended by 20 participants from fishermen and fried food traders. The results of the participant's questionnaire showed that this tool was very useful, at least reducing the use of diesel generators to Rp. 0, - (specifically for lighting purposes at night).